PROJECT DIGITAL EDCATION IN SLOVAKIA - KORMANEC, Vladimir (Journal of Technology and Information Education, 2014)
The article deals with actual homochronous digital of education in Slovakia. It discusses process of digitalization so far and reveals particular phases of project. The article retains the main parts of project as purpose of project, its usage in practice and the asset for recent education and teachers.
Keywords: project digital of education; the digital educational object; teacher; pupil